Pengembangan Aplikasi Click Issues untuk Meningkatkan Hots (High Order Thinking Skills) dalam Ilmu Ekonomi - Annisya' Annisya'; Sri Handayani; Ni'matul Istiqomah; Emma Yunika Puspasari (Jurnal Pendidikan Ekonomi)
The study aims to produce an application that can be used to improve the thinking ability of students or commonly termed HOTS (High Order Thinking Skills). The features provided by this application are related to the topic of existing problems in economics that are being studied. The method used in this research is the ADDIE Research and Development model (Analysis, Design, Development, Implementation, and Evaluation). This research was conducted at the Faculty of Economics, State University of Malang. The appropriateness of the developed application product is based on the assessment of media experts, material experts as well as Economics Faculty-student respondents. The evaluation aspects that are evaluated are related to the material aspects, learning aspects, aspects of the appearance, and operation of the application. The average of all assessments that have been done by experts and students are as follows: 1. Material aspects 85.10%, 2. Learning aspects 87.15%, 3. Display aspects 83.15%, 4. Aspects of application operation 86.51%. The conclusion obtained from these results is the average of the total ratings obtained from the application is 85.47% which shows that this application is suitable for use in economic learning activities.DOI: https://dx.doi.org/10.17977/UM014v13i22020p94